STUDI FENOMENA SLUGGING SEBAGAI INISIASI WATER HAMMER PADA PROSES KONDENSASI UAP DI DALAM PIPA HORISONTAL - , Sukamta, Prof. Dr. Ir. Indarto, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Slugging phenomenon that defined as initiating the water hammer is very interesting study because it has strategic impact on safety factor in industry system and equipment i.e. . pressurized water reactor, heat exchanger, steam or gas transportation in chamical industry, air conditioning, etc. The objective of this research is to investigate the slugging as initiating water hammer phenomena through non directly cantact steam condensing experimental study in a horizontal pipe. The experiment apparatus used in present experimental study consisted of an inner annulus pipe made from copper (din = 17.2 mm, do = 19 mm) with a length of 1.8 m. The outer pipe annulus was a galvanized iron pipe (din = 108.3 mm, do = 114. 3 mm) with a length of 1.6 m. Tested liquid was water. In the experiment, the water was heated using a boiler to generate steam which was then flowed and condensed inside the annulus pipe to form a steam-condensate two-phase flow in horizontal pipe. On the other hand, the water was used as a coolant in the outer of annulus pipe. Thermocouples type K 36 TT OMEGA with chromel (+) and alumel (-) materials were used as temperature sensors, to detect the spread of temperature in circumferential or axial direction along the pipe. The measurement ranged from -50 to 260 oC, with an accuracy of 0.01 Â°C. A data logger of RX 40 serial (OMRON, 20 Channels) was used to record the temperature data with a sampling rate of 5 Hz. The pressure drop axial the test is directly measured using a differential pressure tranducer (validyne, accuracy of Â±0.25%) with a sampling rate of 1.31 kHz. Data of Temperature and differential pressure fluctuations on the steam condensation in a horizontal pipe was analyzed using statistical analysis. For the static pressure Ps=7,5 kPa dan the temperature T = 119,7 Â°C, the results are fo 1). Flow pattern area of non slugging (stratified and wavy flow), transition (wavy-slug flow), and slugging (slug and large-slug). The flow pattern of slug and large-slug are defined as initiating water hammer phenomena, 2). Transition area range of wavy-slug flow pattern are from á¹co=1ï´10-1 kg/s to á¹co= 6ï´10-1 kg/s for á¹st=6ï´10-3 kg/s to á¹st=7.5ï´10-3 kg/s, and á¹co< 3ï´10-1 kg/s for á¹st=8ï´10-3 kg/s to á¹st=9ï´10-3 kg/s. These data are very important to develop the database for input the early warning system design in a safety of two-phase flow installation piping system.